265 Awardee Talk: Maternal and Paternal Contributions to Fertility. (8th October 2021) - Pohler, Ky G; Reese, Sydney T; Franco-Johannsen, Gessica A; de Melo, Gabriela Dalmaso; Filho, Ramiro Oliveira; Poole, Rebecca K
Abstract: Using over 56, 000 pregnancy diagnostic records in beef cattle, a meta-analysis was conducted to objectively determine that 28.4 % of embryos will not develop past day 7 of gestation with most embryonic losses occurring before day 4. Furthermore, by day 30 of gestation, 47.9 % of cows submitted to a single insemination at day 0 will not be pregnant and pregnancy loss between days 32 and 100 was 5.8%. Reproductive success, however, is highly variable and influenced by maternal and paternal factors. Maternal characteristics, including subspecies, parity and reproductive tract size, intersect with breeding management decisions regarding estrus expression and detection to influence conception and pregnancy rates. The maternal endocrine environment, from estradiol associated with estrus around fertilization to elevated prostaglandins during the embryonic to fetal transition period, play critical roles in pregnancy success. Despite the numerous maternal factors involved with pregnancy establishment, sire contribution to reproductive failure should not be overlooked. Sires are reported to influence pregnancy loss during the second month of gestation in both beef and dairy herds. These differences in sire field fertility could not be explained by differences in semen characteristics nor differences in sire conception rate (SCR) score. To understand parental contribution to pregnancy development during the second month of gestation we developed parthenogenetic (PA) embryos (embryos lacking paternal genome). We observed that PA conceptus had well developed trophectoderm tissue at day 31 of gestation but no site of embryo attachment to the endometrium. Moreover, conceptus secretion such as pregnancy-associated glycoproteins and interferon-stimulated genes were not found in maternal circulation. These results suggest that paternal genetics is required for post-elongated embryo attachment to endometrium. Further exploring the maternal vs paternal contribution to pregnancy development can help elucidate the mechanism that drives reproductive failure in cattle.